How we became human : mimetic theory and the science of evolutionary origins (Studies in violence, mimesis, and culture., 2015)
From his groundbreaking Violence and the Sacred and Things Hidden since the Foundation of the World, Ren ̌Girard's mimetic theory is presented as elucidating "the origins of culture." He posits that archaic religion (or "the sacred"), particularly in its dynamics of sacrifice and ritual, is a neglected and major key to unlocking the enigma of "how we became human." French philosopher of science Michel Serres states that Girard's theory provides a Darwinian theory of culture because it "proposes a dynamic, shows an evolution and gives a universal explanation." This major claim has, however, remained underscrutinized by scholars working on Girard's theory, and it is mostly overlooked within the natural and social sciences. Joining disciplinary worlds, this book aims to explore this ambitious claim, invoking viewpoints as diverse as evolutionary culture theory, cultural anthropology, archaeology, cognitive psychology, ethology, and philosophy. The contributors provide major evidence in favor of Girard's hypothesis. Equally, Girard's theory is presented as having the potential to become for the human and social sciences something akin to the integrating framework that present-day biological science owes to Darwin-something compatible with it and complementary to it in accounting for the still remarkably little understood phenomenon of human emergence.